APPROVAL SHEET TEACHERS' QUESTIONS AND STUDENTS' RESPONSES IN EFL CLASSROOM : A Case Study in a Public Senior High School in Bandung - Dzulkarnain, Iskandar (2012)
This study investigated the teachers' questions, students' responses, and questioning strategies in EFL classroom. This study was guided by three research questions: 1) What questions do the teachers usually use in EFL classroom to elicit students' responses ? 2) How do students respond to the teachers' questions during teaching and learning process in the classroom?; and 3) What strategies do the teachers apply when the questions are not understood by the students to create an interactive teaching and learning process? This was a qualitative case study in nature. The setting was in a Public Senior High School in Bandung with two teachers and 90 students as the participants. The data were collected through observations, video recording and field notes. Analyzing data was carried out based on the field note and transcripts of teacher-students' conversation gathered by video recording.It was found that the two teachers used more knowledge questions and comprehension questions than application, inference, analysis, synthesis, and evaluation questions. This study revealed the students responded with verbal and non verbal responses. When the students understood to the teachers' questions, they gave verbal responses by directly answered the questions with their own words or by making the sound without answering the questions such as yelling. When the students could not understand the teachers' questions, they gave non verbal responses such as smiling, head shaking, nodding or even just being silent. This study also revealed that both teachers used various questioning techniques to modify questions such as repetition and decomposition when their questions cannot generate student responses. For further investigation could be focused on teachers' materials and questioning strategies that can produce satisfactory responses from students and increase students' achievement in language learning